MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PENGANTAR KEUANGAN DAN AKUNTANSI - Suba’i Suba’i; Hidayatullah Hidayatullah (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2018)
This research was aimed to describe: (1). The Application of Role Playing Model in accounting subject, (2). The problem and solution in teaching accounting using Role Playing Model, (3). The student results after used Role Playing model.This research used class room action research with two cycles and each cycle consist of four steps: planning, action, observing and reflection. This research used observation sheet and competence test as instrument data collections.The results showed that the Role Playing model could be improve student activity in class, despite of in first cycle faced of free rider and diffusion of responsibility but teacher and observer could find the solution. That teacher gave group task and intensive care for slow learner student. And generally, the Role Playing model could improve the student achievement result.